Speed-planning algorithm and super twisting control for autonomous vehicle steering system - Bacha, Sofiane; Saadi, Ramzi; Ayad, Mohamed-Yacine; Aboubou, Abdennacer (Institute of Advanced Engineering and Science, 2023)
Autonomous vehicle field has seen much development in recent years, especially with the appearance of new efficient control techniques focusing on longitudinal and lateral direction in order to follow a specified trajectory or path. This paper proposes a new systematic control technique to simultaneously generate a suitable speed profile and control the vehicle lateral motion through a predetermined path that considers different driving scenarios representing real-world driving. First, an extended-kinematic model for an autonomous vehicle is designed based on side-slip angle estimation. Then, the proposed technique uses a relationship between lateral error, heading error, and vehicle velocity to generate a suitable steering angle based on super twisting mode control. Second, a speed-planning algorithm is developed to control vehicle velocity. The algorithm uses a strategy for sharp curve identification; then it generates an adequate speed profile depending on the dynamic characteristics of these curves to ensure smooth motion of the vehicle through the whole trajectory. The obtained results from using a speed-planning algorithm with a super twisting controller prove the high performance of this control technique in terms of decreasing errors and respecting passenger comfort.